2013
DOI: 10.1016/j.jcin.2012.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Obstruction Following Transcatheter Aortic Valve Implantation

Abstract: Reported cases of coronary obstruction after TAVI occurred more frequently in women, in patients receiving a balloon-expandable valve, and the LCA was the most commonly involved artery. Percutaneous coronary intervention was a feasible and successful treatment in most cases. Continuous efforts should be made to identify the factors associated with this life-threatening complication to implement the appropriate measures for its prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
188
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 289 publications
(201 citation statements)
references
References 40 publications
4
188
1
8
Order By: Relevance
“…At present these risks vary between 3 and 8 percent, depending on the risk profiles of the patients, the overall clinical experience of the teams, and the type of analyses, i.e. whether they are calculated for selected trials or all-comers experiences (11)(12)(13)(14)(15). The overall assessment of a relatively new therapeutic procedure like T-AVI should be based on populationwide results, which can only be gathered by specific clinical registries.…”
Section: Introductionmentioning
confidence: 99%
“…At present these risks vary between 3 and 8 percent, depending on the risk profiles of the patients, the overall clinical experience of the teams, and the type of analyses, i.e. whether they are calculated for selected trials or all-comers experiences (11)(12)(13)(14)(15). The overall assessment of a relatively new therapeutic procedure like T-AVI should be based on populationwide results, which can only be gathered by specific clinical registries.…”
Section: Introductionmentioning
confidence: 99%
“…In the long-axis (LAX) plane (B), the annulus is measured at the hinge point of the right coronary cusp anteriorly (green arrow). The virtual annulus (red arrow) is measured as a plane perpendicular to the long axis of the oversizing is frequently acceptable (25 (19,(28)(29)(30). Using user-defined (zoom) 3-dimensional volumes, direct planimetry of the annulus using multiplanar reconstruction can be performed.…”
mentioning
confidence: 99%
“…A low position of the coronary ostia with respect to the aortic annulus has been highlighted as one of the most important factors contributing to obstruction of the coronary ostia following TAVR, and it has been suggested that a coronary ostia height of ≤ 10 mm increases the risk of coronary obstruction during TAVR [37][38][39].…”
Section: Reduced Rate Of Av-conduction Impairment and Therefore Decrementioning
confidence: 99%